Ideas in the configuration of reality : The memory as expanded time in artistic practice - Robles-Reinaldos, Gerardo; Ortiz Martínez, Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The reflection that arises presents a vision as how memory emerges in the aesthetic experience interfering in the present and modifying the continuous time. We will try to memory from different visions which, far from being a file or catalog, is presented as an emotional display of the experience. A cognitive exercise that enables printing of intense experiences occurs in artistic practice. The feature that distinguishes a work of art not only is associated with its context but that configures a unique reality either in reception as in its active participation.